2015
DOI: 10.1007/s40616-015-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Training Intraverbal Naming to Establish Matching-to-Sample Performances

Abstract: The current study evaluated whether training intraverbal naming would be sufficient to establish visual-visual matching-to-sample (MTS) performances in college students. In the first experiment, we used a multiple-probe design across stimulus sets to assess whether six participants could match arbitrary visual stimuli (AB) after learning to tact their two experimentally defined classes (A' and B') and then intraverbally relate their names (i.e., BA' goes with B'^). All participants matched the stimuli accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 36 publications
7
34
0
3
Order By: Relevance
“…Overall, these results replicate findings from previous studies demonstrating that tact and intraverbal training can be utilized to establish equivalence classes, as well as novel intraverbal relations consistent with symmetry and transitivity (Ma et al, ; Santos et al, ). This training was also effective to develop generalized equivalence classes, with little or no remedial training necessary.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, these results replicate findings from previous studies demonstrating that tact and intraverbal training can be utilized to establish equivalence classes, as well as novel intraverbal relations consistent with symmetry and transitivity (Ma et al, ; Santos et al, ). This training was also effective to develop generalized equivalence classes, with little or no remedial training necessary.…”
Section: Resultssupporting
confidence: 88%
“…Results of this experiment support previous research evaluating the role of verbal behavior, more specifically intraverbal bidirectional naming (I‐BiN), on the emergence of equivalence classes (Ma et al, ; Santos et al, ). In prior experiments, tact and intraverbal training were effective in establishing responding consistent with the formation of three 3‐member visual equivalence classes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The use of problem solving statements (e.g., “same goes with same”) by some of the participants is consistent with results obtained by Miguel et al () and previous research on bidirectional naming in which intraverbally related stimulus names may evoke correct listener responses during MTS tasks (Jennings & Miguel, ; Ma et al, ; Petursdottir, Carp, Peterson, & Lepper, ; Santos et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Self‐reports from some participants in combination with their responding suggest that our instructions may have influenced the way participants learned baseline relations and how they performed during equivalence test trials. Previous studies have demonstrated that either instructions or participants' self‐generated verbal responses may play an important role in establishing conditional discriminations or responding in accordance with equivalence (Arntzen, ; Arntzen, Vaidya, & Halstadtro, ; Cullinan et al, ; Jennings & Miguel, ; Ma, Miguel, & Jennings, ; Pilgrim, Jackson, & Galizio, ; Santos, Ma, & Miguel, ). Prior to each task, our participants were instructed to touch the comparison if they thought it was “correct” and to not touch the comparison if they thought it was “incorrect.” Subsequent exposure to the reinforcement contingencies in AB/BC training may have established rules for “correct” responding (e.g., A1 always goes with B1 so, if presented with A1, then only touch B1 and vice versa) and these rules may have adversely affected participant behavior during transitivity tests.…”
Section: Discussionmentioning
confidence: 99%